Crystalloid volume versus catecholamines for management of hemorrhagic shock during esophagectomy: assessment of microcirculatory tissue oxygenation of the gastric conduit in a porcine model using hyperspectral imaging - an experimental study - Studier-Fischer, Alexander; Özdemir, Berkin; Rees, Maike; Ayala, Leonardo; Seidlitz, Silvia; Sellner, Jan; Kowalewski, Karl-Friedrich; Haney, Caelán Max; Odenthal, Jan; Knoedler, Samuel; Dietrich, Maximilian; Gruneberg, Daniel; et al. (International journal of surgery, 2024)
Introduction: - Oncologic esophagectomy is a two-cavity procedure with considerable morbidity and mortality. Complex anatomy and the proximity to major vessels constitute a risk for massive intraoperative hemorrhage. Currently, there is no conclusive consensus on the ideal anesthesiologic countermeasure in case of such immense blood loss. The objective of this work was to identify the most promising anesthesiologic management in case of intraoperative hemorrhage with regards to tissue perfusion of the gastric conduit during esophagectomy using hyperspectral imaging. - Material and methods: - An established live porcine model (n=32) for esophagectomy was used with gastric conduit formation and simulation of a linear stapled side-to-side esophagogastrostomy. After a standardized procedure of controlled blood loss of about 1 l per pig, the four experimental groups (n=8 each) differed in anesthesiologic intervention, that is, (I) permissive hypotension, (II) catecholamine therapy using noradrenaline, (III) crystalloid volume supplementation, and (IV) combined crystalloid volume supplementation with noradrenaline therapy. Hyperspectral imaging tissue oxygenation (StO2) of the gastric conduit was evaluated and correlated with systemic perfusion parameters. Measurements were conducted before (T0) and after (T1) laparotomy, after hemorrhage (T2), and 60 min (T3) and 120 min (T4) after anesthesiologic intervention. - Results: - StO2 values of the gastric conduit showed significantly different results between the four experimental groups, with 63.3% (±7.6%) after permissive hypotension (I), 45.9% (±6.4%) after catecholamine therapy (II), 70.5% (±6.1%) after crystalloid volume supplementation (III), and 69.0% (±3.7%) after combined therapy (IV). StO2 values correlated strongly with systemic lactate values (r=−0.67; CI −0.77 to −0.54), which is an established prognostic factor. - Conclusion: - Crystalloid volume supplementation (III) yields the highest StO2 values and lowest systemic lactate values and therefore appears to be the superior primary treatment strategy after hemorrhage during esophagectomy with regards to microcirculatory tissue oxygenation of the gastric conduit.
Online veröffentlicht: 8. Juli 2024
Gesehen am 26.03.2025